History, heritage, and colonialism : Historical consciousness, Britishness, and cultural identity in New Zealand, 1870-1940 - Gentry, Kynan (Book collections on Project MUSE., 2015)
This title explores the politics of history-making and interest in preserving the material remnants of the past in late-nineteenth and early-twentieth-century colonial society, looking at both indigenous pasts and those of European origin.